Isolation of Antimicrobial Peptides from Bornean Frog’s Mucus via High Performance Liquid Chromatography (HPLC) - Muhamad Syafiq, Ahmad Zahari (Universiti Malaysia Sarawak (UNIMAS), 2012)
Bornean frogs are believed to be a rich source of antimicrobial peptides which plays an important role in their skin defence against various kinds of pathogens. In order for the mucus secretion to be analyzed for its constituents, the frogs were entrapped within an empty container which was vaporized with diethyl ether. After being left for over 15 – 20 minutes, the frog was then washed and the washed solution was collected in an empty and sterile beaker. The washed solution was pipetted into an eppendorf in 500µL aliquots. Equal amount of 80% glycerol added into the eppendorf tube to protect the peptides against denaturation. 0.1% TFA and Acetonitrile were used as a buffer for the protein purification. Both the samples and the buffer were sonicated before being run through HPLC. The sample from four different species of frog which are R.nigropalmatus, L. kuhlii, K. pulchra and K. pleurostigma were injected onto a (1 x 25 cm) Vydac 218TP50 (C-18) reversephase HPLC column (separations group) equilibrated with 0.1% (v/v) TFA/water at flow rate of 2.0 mL per minute. The concentration of Acetonitrile in the eluting solvent was raised to 21% (v/v) over 10 minutes and to 63% (v/v) over 60 minutes using linear gradients. The absorbance of the peptides was monitored at 214 nm and 280 nm. The peaks observed from the chromatogram confer with those reported in previous studies and various peptides were identified such as bradykinin, ranatuerin, temporin and brevinin.